OM20190325001


题: 已知\begin{cases} x_1-x_2-x_3-\cdots-x_n=2a, \\ -x_1+3x_2-x_3-\cdots-x_n=4a, \\ -x_1-x_2+7x_3-\cdots-x_n=8a, \\ \cdots\\ -x_1-x_2-x_3-\cdots+(2^n-1)x_n=2^n a.  \end{cases}
用含na的代数式表示x_n.

解: 首先容易证明:

    \[\begin{aligned} &2^{n-2}-2^{n-3}-2^{n-4}-\cdots-2-1-1=0, \\ &-2^{n-2}+(2^2-1)\times 2^{n-3}-2^{n-4}-\cdots-2-1-1=0, \\ &-2^{n-2}-2^{n-3}+(2^3-1)\times 2^{n-4}-2^{n-5}-\cdots-2-1-1=0, \\ &\cdots\\ &-2^{n-2}-2^{n-3}-\cdots+(2^k-1)\times 2^{n-1-k}-2^{n-2-k}\cdots-2-1-1=0, \\ &\cdots\\ &-2^{n-2}-2^{n-3}-\cdots+(2^{n-1}-1)\times 1-1=0, \\ &-2^{n-2}-2^{n-3}-\cdots-2-1+(2^{n}-1)=2^{n-1}.  \end{aligned}\]

所以将原方程式从上至下依次乘2^{n-2}, 2^{n-3}, 2^{n-4}, \cdots, 2, 1, 1, 再相加, 得

    \[2^{n-1}x_n=\big[2^n+(n-1)\cdot 2^{n-1}\big]a=2^{n-1}(n+1)a.\]

    \[x_n=(n+1)a.\]